Septicaemia due to Pasteurella pneumotropica - Rogers, Bogumila T. (1973)
The literature concerning Pasteurella pneumotropica infection in animals and man is briefly reviewed and a case presented in which the organism was the cause of septicaemia in a patient receiving chemotherapy for myeloid leukaemia. Bacteriological findings are recorded and compared with those of other authors.